1989
DOI: 10.1111/j.1398-9995.1989.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical estimations of allergenic activities from outdoor aero‐allergens, collected by a high‐volume air sampler

Abstract: To quantify airborne allergens in amorphus and morphological particles, a survey with collection of aero-allergens on glass fibre filters by means of a high-volume air-sampler (HIVOL) was conducted. In preliminary laboratory experiments we compared various filter elution techniques, and the pulverizing elution technique was found to be optimal with regard to yield and convenience. When a surfactant, Tween 20 (0.5% v/v), was added to the elution buffer, a recovery of 80% could be obtained. Allergens in eluates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…The allergen detection methods used in this and other studies (Agarwal et al 1984, Jensen et al 1989, Spieksma et al 1990) are not very sensitive, and require sampling of relatively high quantities of air. This is particularly true for the collection of most…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allergen detection methods used in this and other studies (Agarwal et al 1984, Jensen et al 1989, Spieksma et al 1990) are not very sensitive, and require sampling of relatively high quantities of air. This is particularly true for the collection of most…”
Section: Discussionmentioning
confidence: 99%
“…However, symptoms of the lower bronchial regions of the respiratory tract, like coughing and wheezing, are also frequently seen in pollen-allergic patients. Although it is plausible that a small number of airborne pollen grains might be capable of penetrating into the lower regions of the respiratory organs (Michel et al 1977), suggestions and evidence for airborne allergenic activity associated with particles smaller than intact pollen grains have been put forward by several authors (Solomon et al 1983, Agarwal et al 1984, Rantio-Lehtimlki et al 1986, Jensen et al 1989. Sampling i f multiple size fractions followed by immuno-assay assessment of airborne grass-pollen allergenic activity has been described only recently (Spieksma et al 1990).…”
mentioning
confidence: 99%
“…Several studies on airborne pollen antigens have been performed using various immunochemical methods, such as IgG-subclass RAST-inhibition (Jensen et al 1989), IgE-RAST (Spieksma et al 1990) and IgG-ELISA (Pehkonen & Rantio-Lehtimiiki 1994, Rantio-Lehtimaki et al 1994. The specificity of these methods has not been investigated in detail.…”
Section: (Maizuscrandt Accepted 5 Sepienzber 1995)mentioning
confidence: 99%
“…(Manuscript accepted 1 September 1997) The allergen load of outdoor airborne grass pollen has been reported to correlate with airborne pollen counts (Jensen et al 1989, Johnsen et al 1992, especially on dry days during the grass pollen season (Spieksma et al 1995). It is also suggested that allergic symptoms in sensitized persons are related to allergen concentration.…”
mentioning
confidence: 99%